SIMULATOR GENERATOR HARMONIK - Sasmoko, Priyo (Vocational School Diponegoro University, 2011)
Priyo Sasmoko, in this paper explain that the need of electric power recently progressively complex, not only the requirement of availability of electricity, but the quality of energy have become prime facie demand. Studies of electricity quality have been conducted by many experts, one of them is about harmonic. Harmonic represent waving current or tension which is tension distortion at electric power system mains so that can result unideal waveform. The study of harmonic required appliance or obyek which need to be checked. In this research Simulator Generator Harmonik is madeÂ a harmonic generator module which can deputize the appliance or obyek yielding harmonic with harmonic component and the THD which can be varried. This module works by dividing one cycle of mains become some slots so it can be got harmonic component as desired. To change the THD,a variation of linear load is used so that the ratio of non-linear load current can be varried. Keywords : Simulator, Harmonic component, THD